2019
DOI: 10.1002/jbt.22376
|View full text |Cite|
|
Sign up to set email alerts
|

Nickel oxide nanoparticles exert selective toxicity on skin mitochondria and lysosomes isolated from the mouse model of melanoma

Abstract: Nickel oxide nanoparticles (NiO‐NPs) are progressively used for an immense number of new applications in modern industries sectors. Nevertheless, the toxic impact of NiO‐NPs has not been clearly elucidated on human melanoma cell lines at the cellular and molecular level. Hence, this study was designed to examine the in vitro cytotoxicity potentials of NiO‐NPs on malignant cutaneous melanoma (MCM) mitochondria. Results revealed that NiO‐NPs significantly increased reactive oxygen species level, lipid peroxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…[38] Our results show a collapse in MMP in OSCC mitochondria exposed to SPIONs, which is in agreement with previous studies showing, that SPIONs and other NPs have the potential to collapse in MMP. [19,39] In addition, collapse in the MMP is considered as one of the consequences of the increase in the level of ROS. In the following, we assessed mitochondrial swelling and cytochrome c release.…”
Section: Discussionmentioning
confidence: 99%
“…[38] Our results show a collapse in MMP in OSCC mitochondria exposed to SPIONs, which is in agreement with previous studies showing, that SPIONs and other NPs have the potential to collapse in MMP. [19,39] In addition, collapse in the MMP is considered as one of the consequences of the increase in the level of ROS. In the following, we assessed mitochondrial swelling and cytochrome c release.…”
Section: Discussionmentioning
confidence: 99%
“…According to our study, NiONPs‐triggered ferroptosis is associated with elevation of lipid peroxidation, depletion of GSH and downregulation of GPX4. Consistently, increased ROS level, lipid peroxidation and mitochondrial membrane potential have been detected on skin mitochondria isolated from mouse melanoma exposed to NiONPs 29 . Exposing HUVECs to NiONPs results in intracellular iron accumulation, which is a sign of pro‐ferroptotic effects 30 .…”
Section: Discussionmentioning
confidence: 68%
“…Consistently, increased ROS level, lipid peroxidation and mitochondrial membrane potential have been detected on skin mitochondria isolated from mouse melanoma exposed to NiONPs. 29 Exposing HUVECs to NiONPs results in intracellular iron accumulation, which is a sign of pro-ferroptotic effects. 30 In addition, Di Bucchianico et al have demonstrated the participation of iron in NiONPs-induced genome instability and cytotoxicity by showing that iron chelator protected against NiONPs-induced chromosomal and cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…NiO-NPs could notably induce optional cytotoxicity on malignant cutaneous melanoma (MCM) mitochondria. Therefore, this compound can be considered a favorable candidate for further in vivo and clinical studies to achieve a novel antimalignant melanoma medicine [ 127 ].…”
Section: Nanotechnology (Metallic and Related Nps) Are Significant To...mentioning
confidence: 99%